SYNERGY OF ISLAMIC BUSINESS ETHICS AND MADURESE CULTURE IN THE MANAGEMENT OF MADURESE GROCERY STALLS : Institut Ummul Quro Al-Islami Bogor - ., Rohman (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
This research examines the implementation of agrarian ethics values, Islamic business ethics in the management of Madurese grocery stalls in urban areas. Using a qualitative method with a multilevel explanatory case study approach, this study found that Madurese grocery stalls adopt Islamic ethical values such as honesty, justice, and social responsibility, which are combined with the hard work ethic and persistence of Madurese agrarian culture. Results show a harmonious integration of Islamic business ethics, Madurese cultural values, and modern business practices, creating a unique and sustainable business model. The success of Madurese grocery stalls is based on strong business ethics principles, the mentality of farmers, the principle of making ends meet, and the ability to maintain traditional values while adapting to the demands of the modern market. The implementation of Islamic business ethics values is seen in the honesty of profit-sharing and reporting systems, fairness of profit sharing, trust in management, willingness in business agreements, and social responsibility. .